Hjemstavn som erindring i migrantlitteratur - Stahr, Radka (Scandinavistica Vilnensis, 2023)
This article focusses on the representation of homeland in two Scandinavian novels: Amal Aden’s Min drøm om frihet (2009) and Jonas Suchanek’s Do danska (2014). Both novels can be considered migrant literature, i.e., literature written by authors who have themselves experienced migration. Another thing that these novels have in common is that their authors construct the image of their original homeland through their own memories. Typically, the idealizing memories are reinforced as the characters are confronted with negative experiences in the new country, where they do not feel assimilated, as we can see it in Aden’s novel. In Suchanek’s novel, nostalgia plays an important role, namely the historical fact that his homeland has actually disappeared (the protagonist emigrated from the communist Czechoslovakia and returns to a completely new post-revolutionary country).Both novels demonstrate the concept of homeland not only as a geographical place, but also in terms of the cultural aspects associated with it, be it friends or food. At the same time, the concept of polygamy of place, which is often mentioned in the context of globalization, does not seem to work very well. Especially in Aden’s novel, the protagonist’s relationship with her original homeland and the new homeland oscillates between topophilia and topophobia. Essential to the memories of the homeland, then, are the triggers that take the characters in both novels back to a time before their migration, creating a sense of discomfort and nostalgia.
Keywords: -